Pengharapan Di Tengah Penderitaan: Sebuah Pendekatan Tematik Terhadap Ayub: 19: 23-27 - Petra Harys Alfredo Tampilang; Kidung Dalu Sriyoko (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2024)
The Book of Job is a book rich with theological reflections on suffering. This is demonstrated in almost every chapter of the book. The richness and depth of its theology compelled the author to conduct this biblical research. According to this study aims this study is to discover the biblical theology of hope in the midst of suffering according to Job 19:23-27. The method used in this study is the thematic method to bring out the minor themes in this text. In addition, the author also use several other analyses such as context analysis, historical analysis, translation analysis, and theological analysis. In this research, the author also investigates various kinds of literature as support. Through this research it was found that there were at least two hopes held by Job when he was in the midst of suffering, namely: First, Job put his hope in God who is his redeemer. Secondly, by focusing on God, Job was able to acknowledge his belief that God would eventually be on his side.